A lithium ion battery
By doping or covering metal elements on the positive electrode material of the lithium-ion battery and forming an interface film layer with cyclic sulfate ester, the problem of ion dissolution of the positive electrode material under high temperature conditions is solved, and the high-temperature circulation and storage performance of the battery is improved.
Patent Information
- Application Number
- CN202011641707.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-31
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-12-31
AI Technical Summary
The ion dissolution problem of the positive electrode material in existing lithium-ion batteries under high temperature conditions leads to deterioration of battery performance, affecting high-temperature storage and cycling performance.
Using a positive electrode active material with a transition metal M, and doping or covering it with a compound containing metal element A, the interface film layer is formed by complexing the cyclic sulfate of a specific structure in the non-aqueous electrolyte to form a surface film layer to stabilize the positive electrode material , prevent unit cell changes and dissolution of metal elements.
The electrochemical performance and cyclic performance of lithium-ion batteries at high temperatures are improved, and the interface film layer formed has high stability in the ratio range of 0.25≤F≤500, avoiding the increase in battery impedance.
Smart Images

Figure FDA0004993019710000011 
Figure FDA0004993019710000012 
Figure FDA0004993019710000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in 3C digital devices and new energy vehicles due to their high energy density, long cycle life, low self-discharge rate, and environmental protection. With the continuous development of modern technology and the continuous expansion of the application scope of lithium-ion batteries, the requirements for energy density of lithium-ion batteries are further improved.
[0003] As the main factor limiting the capacity of lithium-ion batteries, in recent years, positive electrode materials have been continuously improved through crystal doping and surface coating and other technical means to improve the cut-off voltage and applicable temperature range of lithium-ion batteries. However, doping and surface coating will affect the shuttle stability of lithium ions between the electrolyte and the electrode material to a certain extent, thereby affecting the electrochemical performance of the battery. At the same time, the transition metal elements of the positive electrode material itself and the metal elements used for doping or surface coating are easily dissolved in the electrolyte under high temperature conditions and migrate to the surface of the negative electrode material, which will not only destroy the negative electrode SEI film, but also hinder the release of embedded lithium in the negative electrode material, produce lithium dendrites, and directly deteriorate the electrochemical performance of the battery such as high-temperature storage and high-temperature cycling. Summary of the invention
[0004] Aiming at the problem that existing doped or surface-coated positive electrode materials may have ion dissolution under high temperature conditions, which may deteriorate battery performance, the present invention provides a lithium-ion battery.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0006] An embodiment of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, the positive electrode active material comprises LiMO2, wherein M is selected from one or more of Ni, Co and Mn, the positive electrode active material is doped with a compound containing a metal element A and / or the positive electrode active material is coated with a compound containing a metal element A, and the metal element A is selected from one or more of Al, Mg, Pb, Ti, Ba, Cu, Fe, Sr, Y, Zr, Zn, Cd, Ru, V, Mo, Ta, W, Nb and Sn;
[0007] The non-aqueous electrolyte comprises a solvent, an electrolyte salt and a compound shown in structural formula 1:
[0008]
[0009] Among them, E is selected from
[0010]
[0011] Where G* represents the bonding position;
[0012] h is 0 or 1;
[0013] R1 and R2 are each independently selected from a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a group represented by structural formula 2, or a group represented by structural formula 3;
[0014] R3 is selected from an alkyl group having 1 to 6 carbon atoms, a halogenated alkyl group, an alkoxy group, a halogen atom or a group represented by formula 4;
[0015] L is selected from a single bond or a methylene group, W is selected from
[0016] Wherein, m is an integer from 1 to 4, n is an integer from 0 to 2, and p is an integer from 0 to 6;
[0017] Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage content of the compound shown in the structural formula 1 is B%; the ratio of the molar content of the metal element A to the molar content of the transition metal M per unit area of the positive electrode material layer is C, F = B / C, satisfying the following relationship
[0018] 0.25≤F≤500.
[0019] Optionally, the F value satisfies the following relationship:
[0020] 1≤F≤200;
[0021] Preferably, 5≤F≤80.
[0022] Optionally, the positive electrode active material is selected from LiNi x Co y Mn z A (1-x-y-z) O2, wherein A is selected from one or more of Al, Mg, Pb, Ti, Ba, Cu, Fe, Sr, Y, Zr, Zn, Cd, Ru, V, Mo, Ta, W, Nb and Sn, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤x+y+z<1, and x, y and z are not 0 at the same time.
[0023] Optionally, a coating layer is disposed outside the positive electrode active material, the coating layer is selected from oxides containing metal element A, and the weight of the coating layer is 1 to 10% of the total weight of the positive electrode active material.
[0024] Optionally, the oxide containing the metal element A includes one or more of aluminum oxide, magnesium oxide, titanium oxide, tungsten oxide, tin oxide, zinc oxide, zirconium oxide, molybdenum oxide and chromium oxide;
[0025] Preferably, the lattice energy of the oxide containing the metal element A is less than 4000 Kj / mol.
[0026] Optionally, the compound represented by structural formula 1 is selected from one or more of the following compounds:
[0027]
[0028]
[0029]
[0030] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by structural formula 1 is 0.05% to 5%, preferably 0.1 to 3%;
[0031] The range of C is 0.01 to 0.2, preferably 0.01 to 0.1.
[0032] Optionally, the positive electrode material layer further includes a positive electrode binder, and the positive electrode binder includes polyvinylidene fluoride.
[0033] Optionally, the solvent includes one or more of cyclic carbonates, linear carbonates, carboxylates and ethers.
[0034] Optionally, the electrolyte salt includes one or more of LiPF6, LiBF4, LiPO2F2, LiTFSI, LiBOB, LiDFOB, LiTFSI, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiC(SO2CF3)3 and LiN(SO2F)2;
[0035] In the non-aqueous electrolyte, the content of the electrolyte salt is 0.5-3.5 mol / L.
[0036] Optionally, the non-aqueous electrolyte further comprises an auxiliary additive, wherein the auxiliary additive comprises one or more of unsaturated cyclic carbonate, fluorinated cyclic carbonate, cyclic sultone and cyclic sulfate;
[0037] Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the auxiliary additive is 0.1% to 5%;
[0038] Preferably, the fluorinated cyclic carbonate is selected from one or more of fluoroethylene carbonate, trifluoromethylethylene carbonate and bisfluoroethylene carbonate;
[0039] The cyclic sultone is selected from one or more of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone;
[0040] The cyclic sulfate is selected from vinyl sulfate and / or 4-methylvinyl sulfate.
[0041] According to the lithium ion battery provided by the present invention, a positive electrode active material having a transition metal M is used, and at the same time, ions containing metal element A are doped on the positive electrode active material and / or the positive electrode active material is coated with a compound containing metal element A. The inventors have experimentally found that after a cyclic sulfate ester of a specific structure (such as a compound shown in structural formula 1) is added to a non-aqueous electrolyte, the cyclic sulfate ester can complex the cations of the doped or coated metal element A in a certain proportion under the catalysis of the transition metal M, and then form an interface film layer complexed with the cations of the doped or coated metal element A on the surface of the positive electrode material layer, further stabilizing the positive electrode active material, preventing the change of the unit cell of the positive electrode active material in the c / a axis direction, preventing the collapse of the crystalline structure, and improving the overall stability of the material, thereby improving the electrochemical performance of the battery at high temperature.
[0042] Specifically, the ratio between the compound shown in structural formula 1, the transition metal M and the metal element A has a great influence on the stability of the interface film layer formed on the surface of the positive electrode material layer. When the ratio F satisfies the condition 0.25≤F≤500, the formed interface film layer has high stability. Regardless of whether the ratio F is lower or higher than the above ratio range, it is not conducive to improving the stability of the interface film layer. In particular, if the F value is too small, it is difficult to form a complete interface film layer; if the F value is too large, it will lead to an increase in battery impedance. DETAILED DESCRIPTION
[0043] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] An embodiment of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, the positive electrode active material comprises LiMO2, wherein M is selected from one or more of Ni, Co and Mn, the positive electrode active material is doped with ions containing a metal element A and / or the positive electrode active material is coated with a compound containing a metal element A, and the metal element A is selected from one or more of Al, Mg, Pb, Ti, Ba, Cu, Fe, Sr, Y, Zr, Zn, Cd, Ru, V, Mo, Ta, W, Nb and Sn;
[0045] The non-aqueous electrolyte comprises a solvent, an electrolyte salt and a compound shown in structural formula 1:
[0046]
[0047] Among them, E is selected from
[0048]
[0049] Where G* represents the bonding position;
[0050] h is 0 or 1;
[0051] R1 and R2 are each independently selected from a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a group represented by structural formula 2, or a group represented by structural formula 3;
[0052] R3 is selected from an alkyl group having 1 to 6 carbon atoms, a halogenated alkyl group, an alkoxy group, a halogen atom or a group represented by formula 4;
[0053] L is selected from a single bond or a methylene group, W is selected from
[0054] Wherein, m is an integer from 1 to 4, n is an integer from 0 to 2, and p is an integer from 0 to 6;
[0055] Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage content of the compound shown in the structural formula 1 is B%; the ratio of the molar content of the metal element A to the molar content of the transition metal M per unit area of the positive electrode material layer is C, F = B / C, satisfying the following relationship
[0056] 0.25≤F≤500.
[0057] The lithium-ion battery uses a positive electrode active material having a transition metal M, and at the same time, the positive electrode active material is doped with ions containing a metal element A and / or the positive electrode active material is coated with a compound containing a metal element A. The inventors experimentally found that after a cyclic sulfate ester with a specific structure (such as a compound shown in structural formula 1) is added to a non-aqueous electrolyte, the cyclic sulfate ester can complex the cations of the doped or coated metal element A in a certain proportion under the catalysis of the transition metal M, and then generate an interface film layer on the surface of the positive electrode material layer that is complexed with the dissolved cations of the doped or coated metal element A, further stabilizing the positive electrode active material, preventing the change of the unit cell of the positive electrode active material in the c / a axis direction, preventing the collapse of the crystalline structure, and improving the overall stability of the material, thereby improving the electrochemical performance of the battery at high temperatures.
[0058] Specifically, the ratio between the compound shown in structural formula 1, the transition metal M and the metal element A has a great influence on the stability of the interface film layer formed on the surface of the positive electrode material layer. When the ratio F satisfies the condition 0.25≤F≤500, the formed interface film layer has high stability. Regardless of whether the ratio F is lower or higher than the above ratio range, it is not conducive to improving the stability of the interface film layer. In particular, if the F value is too small, it is difficult to form a complete interface film layer; if the F value is too large, it will lead to an increase in battery impedance.
[0059] Among them, the mass percentage content of the compound represented by structural formula 1 in the non-aqueous electrolyte can be quantitatively characterized by methods such as gas chromatography (GC) and ion chromatography (IC); the ratio of the molar content of metal element A to the molar content of transition metal M per unit area of the positive electrode material layer can be qualitatively and quantitatively determined by instruments such as X-ray photoelectron spectrometer (XPS) and inductively coupled plasma spectrometer (ICP).
[0060] In some embodiments, the compound represented by structural formula 1 is selected from R1 and R2 are each independently selected from a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a group represented by structural formula 2, or a group represented by structural formula 3;
[0061] R3 is selected from an alkyl group having 1 to 6 carbon atoms, a halogenated alkyl group, an alkoxy group, a halogen atom or a group represented by formula 4;
[0062]
[0063] Here, G* represents the bonding position.
[0064] In some embodiments, the compound represented by structural formula 1 is selected from Wherein, L is selected from a single bond or a methylene group, and W is selected from
[0065] Herein, m is an integer of 1-4, n is an integer of 0-2, and p is an integer of 0-6.
[0066] Specifically, the compound represented by structural formula 1 is selected from the following structural formulas:
[0067]
[0068] Herein, m is an integer of 1-4, n is an integer of 0-2, and p is an integer of 0-6.
[0069] In a preferred embodiment, the F value satisfies the following relationship:
[0070] 1≤F≤200.
[0071] In a more preferred embodiment, the F value satisfies the following relationship:
[0072] 5≤F≤80.
[0073] In some embodiments, the metal element A is introduced into the positive electrode active material by doping. The doped metal element A can provide a stronger AO chemical bond than active transition metals such as Ni, Co, and Mn, inhibit the precipitation of lattice oxygen under high voltage, and improve the stability of the material structure. The interface film formed by the complexation of the compound shown in Structural Formula 1 and the metal element A can inhibit the dissolution of the transition metal M and the metal element A, further improving the stability of the positive electrode active material.
[0074] In the doped embodiment, the positive electrode active material is selected from LiNi x Co y Mn z A (1-x-y-z) O2, wherein A is selected from one or more of Al, Mg, Pb, Ti, Ba, Cu, Fe, Sr, Y, Zr, Zn, Cd, Ru, V, Mo, Ta, W, Nb and Sn, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤x+y+z<1, and x, y and z are not 0 at the same time.
[0075] In some embodiments, the metal element A is introduced into the surface of the positive electrode active material by coating, and the compound of the metal element A coated on the surface can prevent the direct contact between the positive electrode active material and the electrolyte, thereby avoiding the dissolution of the transition metal; however, in the implementation method of introducing the compound of the metal element A by coating, since the positive electrode active material will have a volume change during the charging and discharging process, it is easy to cause the coating layer to fall off or crack. In this embodiment, the interface film formed by the complexation of the compound shown in structural formula 1 and the metal element A has good affinity with the coating layer, thereby improving the bonding strength between the interface layer and the coating layer, which is beneficial to improving the stability of the coating layer and solving the problem of the coating layer falling off.
[0076] In the coated embodiment, a coating layer is disposed outside the positive electrode active material, the coating layer is selected from oxides containing metal element A, and the weight of the coating layer is 1-10% of the total weight of the positive electrode active material.
[0077] In a preferred embodiment, the oxide containing the metal element A includes one or more of aluminum oxide, magnesium oxide, titanium oxide, tungsten oxide, tin oxide, zinc oxide, zirconium oxide, molybdenum oxide and chromium oxide.
[0078] In a preferred embodiment, the lattice energy of the oxide containing the metal element A is less than 4000 Kj / mol.
[0079] In some embodiments, the compound represented by Structural Formula 1 is selected from one or more of the following compounds:
[0080]
[0081]
[0082]
[0083] It should be noted that the above compounds are only preferred embodiments of the compounds represented by Structural Formula 1 of the present invention and should not be construed as limiting the present invention.
[0084] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by Structural Formula 1 is 0.05% to 5%.
[0085] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by the structural formula 1 is 0.1% to 3%.
[0086] In some embodiments, the range of C is 0.01 to 0.2, preferably 0.01 to 0.1.
[0087] In some embodiments, the positive electrode material layer also includes a positive electrode binder, and the positive electrode binder includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyethylene, styrene butadiene rubber, fluororubber, polyacrylic acid, polyvinyl pyrrolidone, and carboxymethyl cellulose.
[0088] In a preferred embodiment, the positive electrode binder includes polyvinylidene fluoride.
[0089] Compared with other positive electrode binders, the compound shown in structural formula 1 has a better cooperative effect with polyvinylidene fluoride in improving battery performance. It is speculated that the compound shown in structural formula 1 can form a coupling structure with polyvinylidene fluoride to form an intermediate with good mechanical flexibility, which greatly enhances the bonding ability and flexibility of polyvinylidene fluoride, better maintains the integrity of the positive electrode active material, reduces the generation of particle cracks, further improves the structural stability of the positive electrode active material, and greatly improves the electrochemical performance of lithium-ion batteries during the cycle and storage process.
[0090] In some embodiments, the positive electrode material layer further includes a positive electrode conductive agent, and the positive electrode conductive agent includes one or more of carbon black, acetylene black, conductive graphite, carbon nanotubes and graphene.
[0091] In some embodiments, the positive electrode further includes a positive electrode current collector, and the positive electrode material layer is coated on the surface of the positive electrode current collector.
[0092] In some embodiments, the solvent includes one or more of cyclic carbonates, linear carbonates, carboxylates, and ethers.
[0093] In some embodiments, the cyclic carbonate includes one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, and butylene carbonate.
[0094] The linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.
[0095] The carboxylic acid ester includes one or more of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate.
[0096] The ethers include one or more of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0097] In a preferred embodiment, the organic solvent is a mixture of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate.
[0098] In some embodiments, the electrolyte salt includes one or more of LiPF6, LiBF4, LiPO2F2, LiTFSI, LiBOB, LiDFOB, LiTFSI, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiC(SO2CF3)3, and LiN(SO2F)2;
[0099] In the non-aqueous electrolyte, the content of the electrolyte salt is 0.5-3.5 mol / L.
[0100] In a preferred embodiment, the electrolyte salt is selected from LiPF6.
[0101] In a preferred embodiment, in the non-aqueous electrolyte, the content of the electrolyte salt is 0.7-1.5 mol / L.
[0102] In some embodiments, the non-aqueous electrolyte further comprises an auxiliary additive, wherein the auxiliary additive comprises one or more of an unsaturated cyclic carbonate, a fluorinated cyclic carbonate, a cyclic sultone and a cyclic sulfate;
[0103] Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage content of the auxiliary additive is 0.1% to 5%.
[0104] In some embodiments, the unsaturated cyclic carbonate is selected from one or more of vinylene carbonate, vinyl ethylene carbonate, and methylene vinyl carbonate.
[0105] The fluorinated cyclic carbonate is selected from one or more of fluoroethylene carbonate, trifluoromethylethylene carbonate and bisfluoroethylene carbonate.
[0106] The cyclic sultone is selected from one or more of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone.
[0107] The cyclic sulfate is selected from vinyl sulfate and / or 4-methylvinyl sulfate.
[0108] In some embodiments, the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes one or more of metallic lithium, graphite-like carbon materials, hard carbon materials, soft carbon materials, silicon-based, tin-based, antimony-based, aluminum-based, and transition metal compounds.
[0109] In a preferred embodiment, the negative electrode active material is selected from graphite-based carbon materials, and more preferably, the negative electrode active material is selected from artificial graphite.
[0110] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductor.
[0111] The negative electrode binder includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyethylene, styrene butadiene rubber, fluororubber, polyacrylic acid, polyvinyl pyrrolidone, and carboxymethyl cellulose.
[0112] The negative electrode conductive agent includes one or more of carbon black, acetylene black, conductive graphite, carbon nanotubes and graphene.
[0113] In some embodiments, the negative electrode further includes a negative electrode current collector, and the negative electrode material layer is coated on a surface of the negative electrode current collector.
[0114] In some embodiments, the lithium-ion battery also includes a diaphragm, which includes one or more of a polyolefin diaphragm, a polyamide diaphragm, a polysulfone diaphragm, a polyphosphazene diaphragm, a polyethersulfone diaphragm, a polyetheretherketone diaphragm, a polyetheramide diaphragm, and a polyacrylonitrile diaphragm.
[0115] The present invention is further described below by way of examples.
[0116] Example 1
[0117] This embodiment is used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0118] 1) Preparation of electrolyte
[0119] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC=1:1:1, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L, and then various additives were added according to Table 1. The amount of additives used was calculated as a percentage of the total mass of the electrolyte.
[0120] 2) Preparation of positive electrode
[0121] The positive electrode active material, conductive carbon black Super-P and positive electrode binder are mixed in a mass ratio of 93:4:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The positive electrode active material and positive electrode binder are the positive electrode active material and positive electrode binder shown in Table 1, and the slurry is evenly coated on both sides of the aluminum foil, and after drying, rolling and vacuum drying, and welding aluminum lead wires with an ultrasonic welder, a positive electrode plate is obtained, and the thickness of the plate is 120-150μm.
[0122] 3) Preparation of negative electrode plate
[0123] Artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is coated on both sides of the copper foil, dried, rolled and vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain a negative electrode plate with a thickness of 120-150μm.
[0124] 4) Preparation of battery cells
[0125] A three-layer separator with a thickness of 20 μm was placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator was wound. The wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid.
[0126] 5) Battery filling and formation
[0127] In a glove box with water and oxygen contents below 20 ppm and 50 ppm respectively, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left at 45°C for 24 h.
[0128] Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180 min, 0.1C constant current charging for 180 min, 0.2C constant current charging for 120 min, aging at 45°C for 48 h, secondary vacuum sealing, and then further charging at a constant current of 0.2C to the charge cutoff voltage, and discharging at a constant current of 0.2C to 3.0V.
[0129] Embodiments 2 to 18
[0130] Examples 2 to 18 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operation steps in Example 1, except that:
[0131] In the preparation steps of the electrolyte:
[0132] The additives were used in the mass percentages shown in Examples 2 to 18 in Table 1.
[0133] In the preparation steps of the positive electrode plate:
[0134] The positive electrode active materials and positive electrode binders shown in Examples 2 to 18 in Table 1 were used.
[0135] Comparative Examples 1 to 4
[0136] Comparative Examples 1 to 4 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operation steps in Example 1, except that:
[0137] In the preparation steps of the electrolyte:
[0138] The additives were used in the mass percentages shown in Comparative Examples 1 to 4 in Table 1.
[0139] In the preparation steps of the positive electrode plate:
[0140] The positive electrode active materials and positive electrode binders shown in Comparative Examples 1 to 4 in Table 1 were used.
[0141] Performance Testing
[0142] The lithium ion batteries prepared in the above Examples 1 to 18 and Comparative Examples 1 to 4 were subjected to the following performance tests:
[0143] (1) 25℃ impedance measurement method
[0144] The battery was charged at a constant current to 50% of the battery capacity at room temperature (25°C) and maintained for 0.5 hours.
[0145] 0.1C constant current charging for 10s and then resting for 40s, 0.1C constant current discharging for 10s and then resting for 40s, record the end voltage V1;
[0146] 0.2C constant current charging for 10s and then resting for 40s, 0.2C constant current discharging for 10s and then resting for 40s, record the end voltage V2;
[0147] 0.5C constant current charging for 10s and then resting for 40s, 0.5C constant current discharging for 10s and then resting for 40s, record the end voltage V3;
[0148] Draw a straight line with current as the horizontal axis and voltage as the vertical axis. The slope of the straight line is the 25° impedance.
[0149] (2) High temperature cycle performance test
[0150] The prepared lithium-ion battery was placed in an oven at a constant temperature of 45°C, charged at a constant current of 1C to the charge cut-off voltage, then charged at a constant current and constant voltage until the current dropped to 0.05C, and then discharged at a constant current of 1C to 3.0V. This cycle was repeated, and the first discharge capacity and the last discharge capacity were recorded.
[0151] The capacity retention rate of high temperature cycle is calculated as follows:
[0152] Capacity retention rate = last discharge capacity / first discharge capacity × 100%.
[0153] (3) High temperature storage performance test
[0154] The formed lithium-ion battery is charged at room temperature at a constant current of 1C to the charging cut-off voltage, then charged at a constant current and constant voltage until the current drops to 0.05C, then discharged at a constant current of 1C to 3.0V, and the initial discharge capacity of the battery is measured. After fully charged and stored at 60°C for 30 days, the battery is discharged at 1C to 3V, and the retention capacity of the battery is measured. The calculation formula is as follows:
[0155] Battery capacity retention rate (%) = retention capacity / initial capacity × 100%. The test results are entered into Table 1.
[0156] Table 1
[0157]
[0158]
[0159] From the test data of Examples 1 to 18 and Comparative Examples 1 to 4, it can be seen that by using the positive electrode active material and electrolyte additive combination provided by the present invention, especially under the conditions of a limited F value range, the high temperature cycle performance and high temperature storage performance of the battery are effectively improved, while the impedance is maintained at a low level, indicating that the compound shown in Structural Formula 1 and the positive electrode active material doped or coated with metal element A can form an interface film layer with good stability on the surface of the positive electrode material layer under specific proportion conditions, which is beneficial to inhibit the dissolution of metal ions and improve the high temperature performance of the battery.
[0160] From the test results of comparative examples 1 to 11, it can be seen that although the F value has a universal improvement on the high-temperature storage and high-temperature cycle performance of lithium-ion batteries under the condition of 0.25≤F≤500, the extent of the performance improvement varies to a certain extent. When the F value is in the range of 5≤F≤80, the improvement on battery performance is the largest, and the battery is in a state of better comprehensive performance.
[0161] By comparing the test results of Example 8 and Examples 12 to 15, it can be seen that the compounds represented by different structural formulas 1 have a significant performance improvement effect on lithium-ion batteries under the F value conditions specified in the present invention.
[0162] By comparing the test results of Example 8 and Examples 16 to 18, it can be seen that the compound shown in Structural Formula 1 has a good matching effect with the specific binder polyvinylidene fluoride (PVDF), indicating that the compound shown in Structural Formula 1 can form a coupling structure with polyvinylidene fluoride, and the formed intermediate has better mechanical flexibility, which is beneficial to maintaining the stability of the positive electrode active material.
[0163] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: A positive electrode, a negative electrode and a non-aqueous electrolyte are included, wherein the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, the positive electrode active material includes LiMO2, wherein M is selected from one or more of Ni, Co and Mn, and the positive electrode active material is coated with a compound containing a metal element A, wherein the metal element A is selected from one or more of Al, Mg, Pb, Ti, Ba, Cu, Fe, Sr, Y, Zr, Zn, Cd, Ru, V, Mo, Ta, W, Nb and Sn; The non-aqueous electrolyte comprises a solvent, an electrolyte salt and a compound shown in structural formula 1: Among them, E is selected from Where G* represents the bonding position; h is 0 or 1; R1 is selected from a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a group represented by structural formula 2, or a group represented by structural formula 3; R2 is selected from a group represented by structural formula 3 or a group represented by structural formula 2; R3 is selected from the group shown in structural formula 4; L is selected from a single bond or a methylene group, W is selected from Wherein, m is an integer from 1 to 4, n is an integer from 0 to 2, and p is an integer from 0 to 6; Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage content of the compound shown in the structural formula 1 is B%; the ratio of the molar content of the metal element A to the molar content of the transition metal M per unit area of the positive electrode material layer is C, F = B / C, satisfying the following relationship 0.25≤F≤500, and 0.05%≤B%≤5%, 0.01≤C≤0.
2.
2. The lithium-ion battery according to claim 1, characterized in that The F value satisfies the following relationship: 1≤F≤200。 3. The lithium-ion battery according to claim 1, characterized in that The F value satisfies the following relationship: 5≤F≤80。 4. The lithium-ion battery according to claim 1, characterized in that: A coating layer is arranged outside the positive electrode active material. The coating layer is selected from oxides containing metal element A. The weight of the coating layer is 1-10% of the total weight of the positive electrode active material.
5. The lithium-ion battery according to claim 4, characterized in that: The oxide containing the metal element A includes one or more of aluminum oxide, magnesium oxide, titanium oxide, tungsten oxide, tin oxide, zinc oxide, zirconium oxide, molybdenum oxide and chromium oxide.
6. The lithium-ion battery according to claim 4, characterized in that: The lattice energy of the oxide containing the metal element A is less than 4000 Kj / mol.
7. The lithium-ion battery according to claim 1, characterized in that: The compound represented by structural formula 1 is selected from one or more of the following compounds:
8. The lithium-ion battery according to claim 1, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the mass percentage content of the compound represented by the structural formula 1 is 0.1 to 3%; The range of C is 0.01 to 0.
1.
9. The lithium-ion battery according to claim 1, characterized in that: The positive electrode material layer also includes a positive electrode binder, and the positive electrode binder includes polyvinylidene fluoride.
10. The lithium ion battery according to claim 1, characterized in that: The solvent includes one or more of cyclic carbonates, linear carbonates, carboxylates and ethers.
11. The lithium ion battery according to claim 1, characterized in that: The electrolyte salt includes one or more of LiPF6, LiBF4, LiPO2F2, LiBOB, LiDFOB, LiTFSI, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiC(SO2CF3)3 and LiN(SO2F)2; In the non-aqueous electrolyte, the content of the electrolyte salt is 0.5-3.5 mol / L.
12. The lithium ion battery according to claim 1, characterized in that: The non-aqueous electrolyte also includes auxiliary additives, and the auxiliary additives include one or more of unsaturated cyclic carbonates, fluorinated cyclic carbonates, cyclic sultones and cyclic sulfates; Taking the total mass of the non-aqueous electrolyte as 100%, the mass percentage content of the auxiliary additive is 0.1% to 5%.
13. The lithium ion battery according to claim 12, characterized in that: The fluorinated cyclic carbonate is selected from one or more of fluoroethylene carbonate, trifluoromethylethylene carbonate and bisfluoroethylene carbonate; The cyclic sultone is selected from one or more of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; The cyclic sulfate is selected from vinyl sulfate and / or 4-methylvinyl sulfate.
